Study of π-conjugation effect of organic semiconductors on their optical parameters - Ahmad, Z.; Zafar, Q.; Touati, F.; Shakoor, R.A. (Elsevier, 2016)
Metal free organic semiconductor "7,16-bis(3,3-dimethyl-3H-indol-2-yl)-5,14-dihydrodibenzo [b,i][1,4,8,11] tetraazacyclotetradecine" and metal free with extended π-conjugation organic semiconductor "8,19-bis(3,3-dimethyl-3H-indol-2-yl)-6,17-dihydrodinaphthol [2,3-b:2′,3′-i][1,4,8,11] tetraazacyclotetradecine have been synthesized and the effect of conjugation on their photovoltaic parameters have been investigated. The photo-physical study reveals band gaps of 2.61 eV for metal free and 2.16 eV for extended material. The HOMO/LUMO levels of the materials are calculated using cyclic voltammetry (CV) study. The open circuit voltages of metal free and extended materials in single layer photovoltaic cells are observed to be 0.72 and 0.73 under simulated solar light illumination (air mass 1.5 G, 100 mW/cm2), respectively. The short circuit current in the extended materials is found to be more than ∼1.5 times higher the metal free material.